The Effect Of Basel III Decisions On The Classification Of Bank Loan Risks (Field Study On Private Commercial Banks In Syria.) - محمد, رامي (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aimed to demonstrate the effect of Basel (3) decisions on the classification of bank loan risks in private commercial banks in Syria The researcher followed the analytical descriptive approach in his study, and a set of methods including relying on secondary and primary data through a questionnaire designed and distributed to (100) respondents, (90) of which were retrieved, and (87) questionnaires were valid for analysis, and the research community consisted of a cadre Employees at the upper and middle administrative levels in private commercial banks, then the SPSS program was relied upon as a tool for analyzing the available data. The study concluded a number of results, including: The existence of a significant effect between the decisions of Basel 3 and (liquidity risks) in commercial banks, and the existence of a significant effect between the decisions of Basel (3) and market risks in private commercial banks in Syria, and the existence of a significant effect between the decisions of Basel (3) and credit risks in private commercial banks, And the existence of a significant effect between the application of Basel (3) decisions and the classification of bank loan risks